2014
DOI: 10.1002/ange.201311135
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate Clusters Integrated into Peptide Chains and as Inorganic Amino Acids: Solution‐ and Solid‐Phase Approaches

Abstract: General synthetic methods for the grafting of peptide chains onto polyoxometalate clusters by the use of general activated precursors have been developed. Using a solution‐phase approach, pre‐synthesized peptides can be grafted to a metal oxide cluster to produce hybrids of unprecedented scale (up to 30 residues). An adapted solid‐phase method allows the incorporation of these clusters, which may be regarded as novel hybrid unnatural amino acids, during the peptide synthesis itself. These methods may open the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…For increased specificity, click chemistry could be used 34 to conjugate cell-penetrating peptides to the POM to direct the payload to its desired location, further increasing the efficacy of the bioactive POM. 35 …”
Section: Discussionmentioning
confidence: 99%
“…For increased specificity, click chemistry could be used 34 to conjugate cell-penetrating peptides to the POM to direct the payload to its desired location, further increasing the efficacy of the bioactive POM. 35 …”
Section: Discussionmentioning
confidence: 99%
“…A Cu-catalyzed alkyne−azide cycloaddition reaction was then applied to link the clusters together forming linear oligomers in the nanometer range. Yvon et al [275] have reported the Mn III Mo 6 POM with 15 amino acids attached on each side of the POM. The modified properties of the inorganic diamine may be useful in both medical and nano-science research, in specific as recognition motifs and catalytically active sites where key amino acids may be replaced by POM amino acids.…”
Section: An Overview Of Tris-functionalized Hybrid Structuresmentioning
confidence: 98%
“…Among the various POMs, the organic derivatives of polyoxovanadates (POVs) have attracted increasing attentions due to their fascinating catalytic, magnetic properties as well as bioactivities [5][6][7][8]. The combination of POVs and amino acids may improve the bioactivities of the POVs and reduce their toxicity [9,10].…”
Section: Commentmentioning
confidence: 99%